Counseling on Handling Fish Diseases Using Herbal Ingredients at Kakuluk Mesak Fisheries Vocational School, Belu Regency - Andiewati, Suci; Soares, Daniel Candido Da Costa; Anwar, Syaeful; Turnip, Gilbert (Indonesian Journal of Advanced Social Works, 2023)
The fish quality management policy in a fish pest and disease control system aims to protect the continuity of fish cultivation development businesses, produce fishery products that meet quality standards, and protect the sustainability of fish resources. One type of fish that can be cultivated is tilapia and catfish. The main challenge in cultivating them is the diseases and parasites that attack the fish. So far, tilapia disease treatment has used chemicals, which can pollute the environment and people who consume the fish. At the Kakuluk Mesak Fisheries Vocational School, Belu Regency, the use of herbal concoctions to prevent and treat diseases and parasites in tilapia and catfish is the right alternative. The aim of this service is to provide fish farmers with knowledge and skills about the benefits of herbal plants in treating fish diseases and parasites. Garlic, turmeric, betel and papaya leaves are herbal ingredients that can be used to prevent and treat diseases of tilapia and catfish. The methods used include providing instructions and outreach through the distribution of newspapers about fish farmers. The results of the activity showed that ninety percent of the participants understood the material provided, as shown by their responses to questions and their desire to apply what they knew. The conclusion from this service activity is that teachers and students are very interested in the use of herbs in treating diseases of tilapia and catfish.